2020
DOI: 10.1016/j.ctro.2020.05.014
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tongue-deviating and tongue-depressing oral stents on long-term radiation-associated symptoms in oropharyngeal cancer survivors

Abstract: Objectives: To evaluate whether the use of oral stents during intensity modulated radiation therapy (IMRT) for oropharyngeal cancer (OPC) is associated with long-term patient reported symptoms. Materials and methods: Data was obtained from a prospective observational study of disease-free head and neck cancer survivors. Radiation-associated patient reported symptoms were assessed using the MD Anderson Symptom Inventory Head and Neck module (MDASI-HN). Scores of 5 (11-point Likert scale, 0-10) were considered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…Intraoral stents are personalized medical devices designed to position and stabilize the oral cavity to prevent unnecessary irradiation of adjacent tissues. These devices are easy to manufacture [ 193 ] and have been demonstrated to efficiently reduce irradiation of off-target tissues [ 194 , 195 , 196 ]. Salivary glands can be protected from irradiation by temporarily relocating them further away from the field of irradiation in a procedure known as temporary SMG transplantation.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Intraoral stents are personalized medical devices designed to position and stabilize the oral cavity to prevent unnecessary irradiation of adjacent tissues. These devices are easy to manufacture [ 193 ] and have been demonstrated to efficiently reduce irradiation of off-target tissues [ 194 , 195 , 196 ]. Salivary glands can be protected from irradiation by temporarily relocating them further away from the field of irradiation in a procedure known as temporary SMG transplantation.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Recently published studies have also shown the dosimetric advantages of oral stents, including decreased mean and/or maximum dose to non-target areas of the oral mucosa [12]. It was also shown that participants with COTDs had lower toxicityrelated side-effects such as mucositis and xerostomia [12]. It was also shown that participants with stents had lower toxicity-related side-effects such as mucositis and xerostomia.…”
Section: Discussionmentioning
confidence: 96%
“…There is a current, albeit scarce, body of literature that addresses the relationship between COTDs and reduction of radiotherapy toxicities, namely RIOM [11]. Recently published studies have also shown the dosimetric advantages of oral stents, including decreased mean and/or maximum dose to non-target areas of the oral mucosa [12]. It was also shown that participants with COTDs had lower toxicityrelated side-effects such as mucositis and xerostomia [12].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of intraoral stents during radiotherapy of head and neck cancers to avoid unnecessary dose exposure to healthy tissue structures is widely accepted and reported in several case reports and case series [13] , [14] , [16] , [19] , [20] , [25] . While the principles of optimal positioning are well studied, the choice of material has not been investigated systematically.…”
Section: Discussionmentioning
confidence: 99%